Language ideology and language planning in Estonian higher education: nationalising and globalising discourses. Issue 1 (2nd January 2018) - Soler, Josep; Vihman, Virve-Anneli
ABSTRACT: In recent years, interest in the study of language policy issues in the context of universities has grown considerably. One reason for this is the coexistence of two apparently contradictory discourses, centring around nationalising and globalising orientations. Universities are seen by many as the key institutions for safeguarding the sustainability of national languages, while in order to operate on a global scale, an increasing use of foreign languages (particularly English) is necessary in those same institutions. In our paper, we explore the tensions and ambiguities provoked by this scenario in the context of Estonian higher education (HE), focusing on the University of Tartu. More specifically, we look at how different stakeholders orient themselves towards the language question at the university: university officials, members of the university (staff and students), and members of society outside the university. Using discourse analytical tools, we map the ideological constructs with which these different stakeholders take a stance towards the two dominating discourses. In our analysis, we show that these different groups re-create and shape both the nationalising and the globalising discourses currently present in the field of HE by strategically mobilising a set of semiotic resources available to them.